3x+2y=11 ------(a)

5x-4y=11 ------ (b)

Multiply the equation (a) by 2 and add it to equation (b)

2(3x + 2y) + 5x - 4y= 2*11 + 11

6x + 4y + 5x - 4y = 22 + 11

11x = 33

Dividing by 11 on both sides

x = 3

Put value of x in equation (a)

3*3 + 2y = 11

9 + 2y = 11

2y = 11 - 9

2y = 2

Dividing by 2 on both sides

y = 1

So, the values of x and y are 3 and 1 respectively.

5x-4y=11 ------ (b)

Multiply the equation (a) by 2 and add it to equation (b)

2(3x + 2y) + 5x - 4y= 2*11 + 11

6x + 4y + 5x - 4y = 22 + 11

11x = 33

Dividing by 11 on both sides

x = 3

Put value of x in equation (a)

3*3 + 2y = 11

9 + 2y = 11

2y = 11 - 9

2y = 2

Dividing by 2 on both sides

y = 1

So, the values of x and y are 3 and 1 respectively.